Effect of the activating agent on physico-chemical and electrical properties of activated carbon cloths developed from a novel cellulosic precursor - Ramos, M. E. (2011)
Different chemical reagents (phosphoric acid, boric acid, ammonium citrate, sodium dihydrogen phosphate, potassium dihydrogen phosphate, disodium hydrogen phosphate and trisodium phosphate) were employed to develop activated carbon cloths (ACC) by chemical activation of a lyocell precursor, in an attempt to explore their effect on main physico-chemical characteristics and electrical behaviour of the resulting ACC. The activating agent markedly influenced yield, elemental composition, and textural properties of the ACC. The ACC obtained with phosphoric and boric acids were essentially microporous, whereas those developed with the other reagents presented mesoporosity development. Phosphoric acid-derived samples showed the highest specific surface area (976m2/g). The results also highlight the relevance of correcting the external surface adsorption in order to obtain reliable estimates of micropore volume. All the ACC were electrically conductive, their resistivity being also strongly dependent on the nature of the activating agent. The electrical resistivity of the ACC obtained with all the phosphorous compounds was successfully correlated with their C/H ratio and micropore volume.